Analýza trhu ryb a mořských produktů v ČR - Šáchová, Lucie (2009)
Diploma thesis describes the composition of fish meat and its inventions in the diet, shows the development of global fish production and fish consumption and the development of fish consumption in Czech Republic between 1990-2008. This thesis also examines the current product portfolio and provides an overview of entities operating in the Czech market. Based on the questionnaire provides a forecast of probable future trends and possible developments.